Естетичний потенціал гірських ландшафтів: проблеми виявлення, оцінювання, збереження й раціонального використання - Бучко, Жанна Іванівна; Бучко, Нестор Дмитрович (Рахів, 2002)
Aesthetic value of landscapes is main constituent of the recreation and humanistic resource potential of territory or aquatory. Mountain landscapes has considerable aesthetic potential. Proposals of reservation and rational use of aesthetic potential of mountain landscapes are offered.
Aesthetic potential of mountain landscapes: problems of finding, evaluation, reservation and rational use
Keywords: Гірські ландшафти; естетичний потенціал; раціональне використання ресурсів